A comparison of training and match play external load during a congested in-season period in English League 2 football - Fleming, A.; Walker, M.; Armitage, M.; Connor, M.; Beato, M. (The Journal of Strength and Conditioning Research, 2023)
This study aimed to investigate if external training load metrics differ between training days and match day (MD) during a period of fixture congestion and to verify if external load metrics vary based on playing positions. Training and MD data were collected in a part of the competition phase of the 2020-2021 season (6 weeks) in the English Football League 2 (N = 20 players, mean ± SDs: age = 24.4 ± 4.7 years). Global Navigation Satellite System units (Catapult S7 Vector 10 Hz) were used to monitor external load metrics. The metrics were duration of training, total distance (TD), high-speed running distance (HSR), sprinting distance, relative intensity (m/min), total accelerations (TotAcc) (>3 m·s-2), and total decelerations (TotDec) (<-3 m·s-2). This study found that duration, TD, relative intensity, HSR distance, sprint distance, TotAcc, and TotDec were different (p < 0.001, d = small to moderate) between MD and match day minus two (MD-2) or match day minus one (MD-1); however, during match day minus four (MD-4), only relative intensity was significantly lower (p < 0.001) compared with MD output. Therefore, MD-4 was the most demanding training session of the week (after the MD), and during MD-2 and MD-1, coaches decreased players' load to favor players' readiness. Moreover, this study found that MD and MD-1 resulted in statistically different values across several metrics between different playing positions (defenders < midfielders and strikers), whereas metrics in MD-4 and MD-2 were not statistically different, which highlights that in these sessions, players have similar external loads independently from their playing positions.